Novel duck reovirus exhibits pathogenicity to specific pathogen-free chickens by the subcutaneous route - Kexiang Yu (Nature Portfolio, 2021)
Abstract To study the pathogenicity of new duck reovirus (NDRV) to chickens, eighty 3-day-old SPF chickens were equally divided into two groups. The experimental group was inoculated with a NDRV challenge strain of 100 μL (10–5.00 ELD50/0.1 mL) by the subcutaneous (s.c.) route, and the control group was inoculated with 100 μL of sterile phosphate-buffered saline (PBS) by the same route. In the experimental group, chickens exhibited introflexion of claws, performing of splits, stunting syndrome, weight loss and death. Gross lesions such as enlargement and yellowish-white focal necroses were observed in the liver and spleen. Microscopic changes were typical including varying degrees of hepatocyte steatosis and necrosis, splenic lymphocyte necrosis, interstitial pneumonia. Viral loads were detected in lung, liver, heart, spleen, duodenum, burse and kidney. The liver and spleen viral loads remained a much higher level and maintained for a longer time, suggesting that these tissues might be the target organs. In summary, NDRV can cause systemic infections and death in chickens, which indicated that chickens may be infected by NDRV in poultry production.